El arbitraje internacional de inversiones y la lucha internacional contra la corrupción - Carbajal Valenzuela, Christian; Mendoza Neyra, Yolanda (Pontificia Universidad Católica del Perú. Fondo Editorial, 2021)
Within international investment arbitrations, international protection is usually denied to investments that have been made through acts of corruption as the majority of the investment arbitration tribunals do not assume jurisdiction or the claims are considered inadmissible. These decisions, inevitably and indirectly, lead to the exoneration of international responsibility of the defendant States due to the corruption of their public officials, even when these illicit acts are not configured unilaterally, existing, in most cases, shared responsibility between the investor and the State. By not sanctioning corruption, the current crisis in the investment dispute resolution system is aggravated, which, on the contrary, requires urgent and consensual solutions to guarantee a viable reform. Faced with this worrying scenario, this article examines mechanisms to achieve the confluence between International Investment Law, International Anti-Corruption Law and the international standards concerning the Responsibility of States for Internationally Wrongful Acts. We argue that if illicit behavior by public officials is found, depending on the circumstances of each case, the investment arbitration tribunals should rule on the international responsibility of the defendant States for failing to comply with the obligations arising from the International Anti-Corruption and Investment Treaties. Likewise, depending on the case, they must sanction investors and States, since both parties may be responsible for committing the illicit acts of corruption. Recognizing the limitations inherent to the powers of arbitral tribunals, it is possible to affirm that they cannot remain outside the international fight against corruption, as it has been agreed by the international community in the treaties that exist on this matter, being this the situation when the tribunals declare their lack of jurisdiction, avoiding to decide on the acts of corruption identified within the specific case.

En los arbitrajes internacionales de inversión, usualmente se niega la protección internacional a las inversiones efectuadas mediante actos de corrupción al declararse la mayoría de tribunales arbitrales de inversión sin jurisdicción o inadmisibles las demandas. Estas decisiones, inevitablemente, en forma indirecta, conllevan a la exoneración de responsabilidad internacional de los Estados demandados por la corrupción de sus funcionarios públicos, aun cuando estos delitos no se configuran de manera unilateral pues existe, en la mayoría de los casos, responsabilidad compartida entre el inversionista y el Estado. Al no sancionarse la corrupción, se agrava la actual crisis del sistema de solución de controversias de inversión, la misma que, por el contrario, requiere de soluciones consensuadas y urgentes que garanticen una reforma seria y sostenible. Ante este preocupante escenario, se examinan en este artículo mecanismos para lograr la confluencia entre el derecho internacional de las inversiones, el derecho internacional anticorrupción y las normas internacionales sobre responsabilidad internacional de los Estados por hechos ilícitos. Sostenemos que si se comprueban comportamientos ilícitos de funcionarios públicos, dependiendo de las circunstancias de cada caso, los tribunales arbitrales de inversión deben pronunciarse sobre la responsabilidad internacional de los Estados demandados por incumplir las obligaciones emanadas de los tratados internacionales anticorrupción y de inversión. Asimismo, dependiendo del caso, deben sancionar a inversionistas y Estados, puesto que ambas partes podrían ser responsables de la comisión de delitos de corrupción. Reconociendo las limitaciones propias de las facultades de los tribunales arbitrales, es posible afirmar que estos no deben mantenerse al margen de la lucha internacional contra la corrupción, conforme a lo acordado por la comunidad internacional en los tratados existentes sobre la materia, siendo esto lo que ocurre cuando se declaran sin jurisdicción, evitando pronunciarse sobre los actos de corrupción identificados en el caso concreto.
International investment arbitration and the international fight against corruption
Keywords: Corrupción; Responsabilidad internacional de los Estados; Derecho internacionalde las inversiones; Tratado de inversión; Cláusula anticorrupción; Doctrina de clean hands; Abuso de derecho; Principio general del derecho internacional; Arbitraje internacional de inversiones; https://purl.org/pe-repo/ocde/ford#5.05.01